ANALISIS YURIDIS PENGADAAN TANAH UNTUK KEPENTINGAN UMUM - Soraya, Thalia Firda; Amarini, Indriati (LPPM STIH Awang Long, 2023)
Land acquisition by the government for development purposes, especially to realize a just and prosperous society, is a complex action that involves the rights of certain parties, namely the people who have rights to the land. In 2012, the Government of Indonesia passed Law No. 2/2012 on Land Acquisition for Development in the Public Interest. This law is designed to ensure the protection of the rights of each party, both the government and the community, in the land acquisition process. The principles of land acquisition, as explained in the general explanation of Law No. 2/2012, are expected to be in accordance with the values of Pancasila which aims to ensure justice for all parties. This research aims to analyze land acquisition procedures based on Supreme Court Decision Number 482 K/TUN/2021 with reference to Law Number 2 of 2012 on Land Acquisition for Development in the Public Interest. The research method used is normative juridical, a legal research approach that emphasizes literature analysis. The results show that in the land acquisition process, there are stages of planning, preparation, implementation, and delivery of results, which are then determined through the issuance of a Governor Decree.